Coal blending selection for CFPP fuel with slagging fouling prediction and procurement cost calculation. Issue 1 (November 2021) - Hariana,; Putra, H P; Raksodewanto, A A; Enjang,; Kuswa, F M; Darmadi, D B; Nielsen, C
Abstract: Most coal-fired power plants in Indonesia use medium and low-rank coal due to coal availability in the domestic coal market. Because of technical and economic reasons, single coal as fuel is rarely used in coal-fired power plants. Therefore the coal blending method is used. Here, the most dominant technical requirement of a coal-fired power plant is the calorific value and potential of slagging and fouling. For this reason, a selection method that involves the technical aspect of coal and coal procurement cost is carried out. This study found that from 42 types of alternative coal blend made, 18 types fulfill the potential of slagging and fouling criteria. 12 type coal blends could be prioritized as the main alternative because they fulfilled all technical aspects and coal procurement costs. The conclusion obtained from this study is the completion of the search for alternative coal blends based on technical aspects, especially slagging and fouling and procurement cost, to effectively obtain blending priority. This method can be developed for different coal-fired power plant technology and operation condition.